Optimizing The Form Of Murabaha Financing In Baitul Maal Wat Tamwil (Bmt) Towards Sharia-Based Local Economic Inclusion - Sabirin, Yoga Basyiril; Zen, Muhamad (ASAS, 2024)
This article aims to analyze the optimization of the murabaha agreement form in Baitul Maal Wat Tamwil (BMT) and its relevance in supporting the economic growth of sharia-based communities, especially for micro, small and medium enterprises. With a significant number of middle and lower class people in Indonesia, BMT is present as an alternative Islamic financial institution that provides access to usury-free financing. The murabaha agreement allows BMT to purchase goods at the customer's request and sell them at an agreed profit margin. However, there are challenges in the implementation of this financing, hence the need for optimization for BMT managers in an effort to maintain its existence. This research uses a qualitative method with a literature study approach, identifying the mechanism, dynamics of murabaha financing and the role of murabaha in the economy based on DSN-MUI fatwa No. 04/DSN-MUI/IV/2000. The results showed that transparency, customer education, and technology utilization play an important role in increasing trust in BMT while increasing economic inclusion, thus strengthening its position in the Islamic financial system in Indonesia.Keywords: BMT; Murabaha; Sharia Financing